Prospects of using artificial intelligence in researching titanium, aluminum and magnesium alloy powder as dual–use goods - Kiose, Michael; Кіосе, Михайло (Одеса : НУ «ОЮА», 2026)
The abstracts consider the possibility of using artificial intelligence at the stage of analyzing significant amounts of information during the study of titanium, aluminum, and magnesium alloy powders.
Michael K. Prospects of using artificial intelligence in researching titanium, aluminum and magnesium alloy powder as dual–use goods. Криміналістика майбутнього: цифрові інновації, штучний інтелект, глобальні виклики та загрози: збірник матеріалів міжнар. наук.–практ. конф. (м. Одеса, 5 черв. 2026 р.) / заг. ред. С. Ківалова, М. Аракеляна. Одеса : НУ «ОЮА», 2026. С. 253-257. URL: https://doi.org/10.32837/11300.33543
Keywords: dual–use goods; military goods; metal alloy powders; artificial intelligence